Permodelan Simulasi Parametric untuk Menentukan Panduan Rancang Kota - Djimantoro, Michael Isnaeni (Bina Nusantara University, 2015)
The development of the city is along with population growth in the city, from low density into a higher density. Along with the development of the population of the city that is denser, it is necessary to change the pattern of development, where the trend today is leading to the vertical development although increasing the density of the area is not an easy thing. This is because an increase in the density of the area must be balanced with an increase in facilities and adequate infrastructure. If it is not fulfilled then it will have a negative impact on the city or region. One of the necessary infrastructure for the development is transportation infrastructure since the development of a city will increase density therefore in turn it will generate the daily trip, both from the region and towards the region. In the field of urban design, the formula for the density limitation is set in the urban design guidelines that functions as the foundation for an architect to design the building. Urban design guidelines is mainly formulated in the numbers BCR, FAR, and the maximum height of buildings that will form the frame of the building mass. Therefore, this paper intends to explain the optimum modeling between the density of a region with the treshold of existing road infrastructure. With the modeling of the optimum, then the negative impacts can be reduced and the modeling results will get the maximum density that can be accommodated in an area.